Gamification to Engage Healthy Habits in Socially Deprived Secondary School Students - José M. Rodríguez-Ferrer; Ana Manzano León; Pedro Tadeu; Rubén Camacho-Sánchez; José M. Aguilar-Parra (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
A sedentary lifestyle, unhealthy eating habits, and substance abuse are increasingly prevalent among adolescents, necessitating effective interventions within educational environments. This study aimed to assess the effectiveness of a fifteen-week gamified intervention to promote healthy habits among 314 secondary school students residing in socially deprived areas. The gamified PBL (Points-Badges and Leaderboard) approach offers a promising strategy to engage students, enhance their knowledge, and influence their physical activity, nutrition, and substance consumption behaviors. Employing a pre-post-test design with a control group, data were collected through Kimed and IPAQ questionnaires evaluating participants' habits. Results revealed statistically significant differences between pretest and post-test scores in the experimental group and significant differences favoring the experimental group. Participating students exhibited improved physical activity and nutrition, alongside a reduction in harmful substance consumption behaviors. These findings suggest that the gamified PBL intervention holds promise in promoting healthier habits among secondary school students, specifically in socially deprived areas, emphasizing the importance of integrating such interventions into educational curricula.